Self-relevance enhances the benefits of attention on perception - Macrae, C. Neil; Visokomogilski, Aleksandar; Golubickis, Marius; Sahraie, Arash (Visual cognition, 2018)
Considerable efforts have focused on elucidating the influence that self-relevance exerts on perceptual decision-making. To explore this issue further, the current research explored the extent to which stimulus applicability facilitates the benefits of covert attention on early visual processing. In two experiments, we manipulated the personal-relevance of peripheral cues (i.e., geometric shapes) that preceded the appearance of target stimuli (i.e., Gabors) and asked participants to report the orientation of the stimulus with the highest contrast. The results revealed a significant effect of self-relevance on task performance. First, compared to cues associated with a friend or stranger, self-relevant cues enhanced the apparent contrast of a stimulus. Second, the benefits of self-relevance were most pronounced when cues pertained to identities that were significant (vs. trivial or irrelevant) to observers. Together, these findings demonstrate that self-relevance potentiates the benefits of transient attention on stimulus processing.